Shortcomings in Arabic Language Teaching from Social Perspective - Fathurrahman Masruhan (Jurnal Alfazuna : Jurnal Pembelajaran Bahasa Arab dan Kebahasaaraban, 2015)
Learning Arabic language had many social inhibitions. All of teachers regained it consciously or unconsciously. Teachers had a great responsible to identify this case absolutely because it decided the successful of learning process for student or student of university. It can be analogized by a doctor who diagnosed his patient than gave a nice prescription for his disease. How far the accurate diagnosis was received? it helped the doctor to give the accurate composition of medicine as well.Here was the result of research that author did to fulfill a part of task in writing scholarly paper at Wadi Niel Sudan University to finish doctoral study. It’s well known that some of inhibitions in mastering Arabic language in the field of social were firstly? a lot of moslem community turned away from learning Arabic it self. Some of them said that Arabic was difficult to study? and the others toke that Arabic was not so useful for their life? and the other ones said that no time for studying Arabic although it was useful for their life. They were so busy with their daily work so they couldn’t increase their ability in Arabic any more.Secondly? The Dutch and Japanese colonization had a huge influence for Indonesian nation. Hundreds of years they colonized Indonesia and used up the country’s wealth. They made Arabic as a foreign and strange language and had it forbidden to communicate in the field of social or government at all. Thirdly? There was a wrestling between languages in society. There was effort to introduce and make local languages to be familiar in all societies. But the most important thing that these social inhibitions were not negative case all? it showed that teacher was obligated to do something in strengthening other sides to face the matters above.